10-year diagnosis-specific antibiotic prescribing trends among paediatric inpatients at two private-sector hospitals in central India: a prospective observational study - Cecilia Stålsby Lundborg; Megha Sharma; Sarah Van De Weyer (BMJ Open)
Objectives To analyse, compare and present the 10-year diagnosis-specific antibiotic prescribing trends for paediatric inpatients at a non-teaching hospital (NTH) and a teaching hospital (TH) in India.Design and setting A prospective, observational study of antibiotic prescriptions in paediatric departments of two private-sector hospitals in central India. Inpatients were grouped into clinically confirmed infections, suspected infections and no infections.Outcomes Patients in the NTH and TH and duration of antibiotic prescription, the ratio of prescribed daily dose and defined daily dose i.e. PDD* per 100 bed days, diagnosis-specific patterns and trends, adherence to the Access, Watch and Reserve (AWaRe) classification and prescribing guidelines with significant p value<0.05.Results Of 19 027, 17 458 inpatients aged less than 18 years stayed at least one night (NTH: 11 415 and TH: 6043). More patients were prescribed antibiotics in the NTH than in the TH (NTH: 80%, TH: 23%, p<0.001) and had shorter antibiotic treatment (NTH: 3 days, TH: 5 days, p<0.001). In the NTH, 43% of prescribed antibiotics were ‘Not recommended’; in the TH, 56% were from the ‘Watch’ group (AWaRe). Ceftriaxone with a beta-lactamase inhibitor (‘Not recommended’, 39%) was most prescribed in the NTH, and ceftriaxone (‘Watch’, 31%) in the TH.The reduction in the prescription rates of the most prescribed antibiotic classes for PDD*/100 bed days was observed over 10 years, for infectious acute gastroenteritis, typhoid fever and lung infections, especially in the NTH. For hernia patients, the antibiotic prescribing trend of third-generation cephalosporins increased significantly (β=0.13, p=0.02) while decreased for second-generation cephalosporins (β=0.002, p=0.01). The trends decreased in both hospitals for the most common confirmed infections over 10 years.Conclusion This decadal study observes the practices of overuse of antibiotics in both hospitals yet more in the NTH. High prescribing rates of the ‘Not recommended’ and ‘Watch’ warrant understanding the underlying reasons for targeted interventions. Nonetheless, a significant overtime decrease in prescribing antibiotics for infectious diagnosis indicates the potential for the success of antibiotic stewardship in the future.